Effectiveness of Diode Laser versus Intense Pulsed Light in Hirsutism: A Prospective and Comparative Study in Samawa City - A.Abdul-hussein, Arwaa; Azhar Razzaq, Safa; Hamid Shak, Haidar (International Journal of Psychosocial Rehabilitation, 2020)
Lasers are widely used for hair removal. But the choice of the right laser for the right skin type is very important. The aim of this study is to compare the efficacy of diode lasers and intense pulsed light (IPL) on hair removal. Patients and Methods: Fifty female patients with hirsutism were selected for a randomized controlled study in Samawa city at Al-Muthana government. The patients were divided into two groups; in group I, the patient’s diode laser was used; in group II, intense pulsed light (IPL) was used. The patients were evaluated at 1st, 3rd, and 6th months after the last session was done, and medical history, hormonal assay, and abdomino-pelvic ultrasonography were performed to differentiate between idiopathic and pathological hirsutism. Hair thickness, rate of hair reduction and regrowth, and patient satisfaction questionnaire were recorded by using hair counts before treatment and during the period of follow-up. Results: It was seen that the percentage of hair reduction after two sessions of treatment was maximum (45%) in the diode laser group and 30% in the IPL group. The percentage of hair reduction after four sessions of treatment was maximum (58%) in the diode laser group, followed by 37% hair reduction in the IPL group. The percentage of hair reduction after six sessions of treatment was maximum (80%) in the diode laser group, followed by 42% hair reduction in the IPL group. Conclusions: The number of hair follicles and shafts was significantly decreased with the diode laser and IPL, but the diode laser was more effective. No dangerous or permanent damage was observed with both methods.